2022
DOI: 10.3201/eid2801.211682
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 and Respiratory Virus Sentinel Surveillance, California, USA, May 10, 2020–June 12, 2021

Abstract: State and local health departments established the California Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Respiratory Virus Sentinel Surveillance System to conduct enhanced surveillance for SARS-CoV-2 and other respiratory pathogens at sentinel outpatient testing sites in 10 counties throughout California, USA. We describe results obtained during May 10, 2020‒June 12, 2021, and compare persons with positive and negative SARS-CoV-2 PCR results by using Poisson regression. We detected SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…A recent study of COVID‐19 test positivity using surveillance data from the California severe acute respiratory syndrome coronavirus 2 and respiratory virus sentinel surveillance system from sentinel outpatient testing sites in 10 counties throughout California, found that several occupational groups with high proportions of essential workers showed some evidence of higher test‐positivity. 22 These higher‐risk occupations were consistent with mortality data on workers in California. 23 Furthermore, they were consistent with findings from the current study for workers across the United States.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A recent study of COVID‐19 test positivity using surveillance data from the California severe acute respiratory syndrome coronavirus 2 and respiratory virus sentinel surveillance system from sentinel outpatient testing sites in 10 counties throughout California, found that several occupational groups with high proportions of essential workers showed some evidence of higher test‐positivity. 22 These higher‐risk occupations were consistent with mortality data on workers in California. 23 Furthermore, they were consistent with findings from the current study for workers across the United States.…”
Section: Discussionsupporting
confidence: 79%
“…Although there was no information on hospitalization for COVID‐19 in the current study using the Delphi US CTIS data, the test positivity percentages for COVID‐19 up to the end of November 2020 for nurses and nursing assistants were among the highest for healthcare personnel. A recent study of COVID‐19 test positivity using surveillance data from the California severe acute respiratory syndrome coronavirus 2 and respiratory virus sentinel surveillance system from sentinel outpatient testing sites in 10 counties throughout California, found that several occupational groups with high proportions of essential workers showed some evidence of higher test‐positivity 22 . These higher‐risk occupations were consistent with mortality data on workers in California 23 .…”
Section: Discussionsupporting
confidence: 52%
“…These patterns of respiratory virus circulation from 2019-2021 mirror the trends in HCoV observed in SFS, a community-wide surveillance study of respiratory pathogens 27 and a county level surveillance study in California. 28 Despite consistent participant enrolment throughout the summer months, HCoV was not detected again until January 2021, a delay compared to the previous year. The US National Respiratory and Enteric Virus Surveillance System (NREVSS), a passive surveillance network, provides regional and national surveillance of HCoV.…”
Section: Discussionmentioning
confidence: 97%
“…The recognition of HCoV burden across the age spectrum and the use of molecular testing in community respiratory viral surveillance has facilitated an improved understanding of HCoV burden at the local, 26 , 27 regional 28 and national levels. 29 Our study offers a unique look at HCoV detection before and during the COVID-19 pandemic in homeless shelters.…”
Section: Discussionmentioning
confidence: 99%
“…During the 2019-2021 SARS-CoV-2 pandemic, social distancing and masking protocols to reduce coronavirus transmission resulted in significantly lower numbers of respiratory syncytial virus and influenza virus infections. This was not the case for HRV (2)(3)(4). Rhinovirus infections are currently an inevitable part of life for humans of all ages, with an expected one to two rhinovirus infections per year over an average lifespan (5).…”
Section: Introductionmentioning
confidence: 99%